External Factors Influence on Defects Detection by Scanning Contact Potentiometry - A. I. Alwaheba; V. I. Surin (Annals of "Dunarea de Jos" University of Galati, Fascicle XII, Welding Equipment and Technology)
Scanning contact potentiometry (SCP) method was used to detect structural inhomogeneities in a welded joint under the application of heat and constant electric current. For this purpose, a special sample was prepared, welded by manual arc welding from two halves of X8CrNiTi18-10 (Chromium-Nickel-titanium stainless Steel) austenitic steel, each with dimensions of 200×110×13.5mm. After welding, welded sample was inspected using X-ray radiography. The sample was stored for five months at room temperature, and the sample surface was scanned using different scanning speed ranging from 0.36 to 1.8 mm/sec. It was found that when scanning speed was increased, the signal values remained the same. In another experiment, a constant electric current was passed through the sample from 0.01 to 0.1A. Applying current led to the excitation of weak structural inhomogeneities from the welding joint butt, although it was machined. While heat led to an increase in diagnostic signal amplitude.